Combined Effect of the Core-Shell Structure and Variable Wettability in Polymer Fiber Membranes for Dual and Delayed Release of Active Agents - Hamm-Hahn, L (American Chemical Society, 2024)
Developing polymeric membranes capable of modulating the release of compounds by controlling their surface properties and structure represents an important challenge for efficient drug and active agent delivery systems. Herein, we combine the two properties of polymeric fibers, on the one hand, the core-shell structure and, on the other hand, the control of wettability, to manufacture polymeric membranes with dual and delayed release capacity of active agents. Fibers consisted of a shell of derivates of poly(styrene-co-maleic anhydride) functionalized with amino acids of different hydropathic indexes and loaded with silver nanoparticles and a core of poly(vinyl alcohol) containing allantoin, both used as antibacterial and healing active agent, respectively. Silver ion release profiles were characterized by two regimes that were reminiscent of the core-shell structure of the fibers. An initial lag phase governed by diffusion was followed by a higher release rate driven by a diffusion front of allantoin from the center of the fiber until it reached the external environment. The allantoin release profiles were well-fit by a first-order model, where the saturation value was related to the wettability of the membranes. Our results show how the control of wettability and the core-shell configuration of the fibers may be a strategy for creating a versatile polymeric platform for a fine-tuned release of active agents for biomedical applications. © 2024 American Chemical Society.